Nutritional supplementation with arginine protects radiation-induced effects. An experimental study - Pinto,Flavia Cristina Morone (2016)
ABSTRACT PURPOSE: To investigate the protective effect of L-arginine on the prostate (nonneoplasic) of rats with radiation-induced injury. METHODS: Twenty-nine Wistar rats, male adult, allocated into three groups: Control group (C) was not exposed to irradiation (n=10); Radiated group (R) had undergone pelvic irradiation (n=10); Supplemented and radiated group (R+S) had undergone pelvic irradiation plus L-arginine supplementation (n=9). The animals were observed for signs of toxicity. After euthanization, the prostate was dissected under magnification and stained by hematoxylin and eosin to study acinar structures and stained with Picrosirius red for collagen analysis. RESULTS: After radiation exposure, all animals presented diarrhea, but supplementation with L-arginine reduced this effect. The weight gain in the R+S group was significantly higher than in the C and R groups. In the R+S group the collagen density and the prostate acinar area was similar to the R and C groups. Epithelial height was significantly reduced in group R compared with group C (p<0.0001). When comparing the group R+S with R, a statistical difference was observed to be present (p<0.0001). CONCLUSIONS: Pelvic radiation promotes systemic effects and some structural modifications in the ventral prostate of rats. These modifications can be prevented by oral supplementation with L-arginine.